SINKRONISASI MATERI PASAL 31 PERPOL 4/2020 DENGAN PASAL 151A UU 6/2023 CIPTA KERJA DALAM IMPLEMENTASI PENGAMANAN SWAKARSA NASIONAL: Synchronization of Article 31 Perpol 4/2020 with Article 151A of Law No. 6/2023 on Job Creation in implementation - Najib Rais Rodhiansyah; Ferry Edwar (Faculty of Law, Universitas Trisakti, 2026)
The synchronization between Article 31 of Police Regulation Number 4 of 2020 on Community-Based Security and Article 151A of Law Number 6 of 2023 on Job Creation is important to ensure legal certainty for security guards as strategic security personnel. Differences in regulatory scope often lead to irregularities in guidance, assignment, and employment relations. This study formulates the problem of how the alignment of these two provisions operates in normative implementation and in the practice of security guard employment relations. The research aims to analyze the coherence of the two regulations using a normative juridical approach by examining applicable laws and regulations. The results indicate the existence of implementation inconsistencies, particularly concerning retirement age limits, training standards, and the absence of integration of Police Regulation provisions into employment contracts, company regulations, or collective labor agreements. These obstacles are further exacerbated by weak inter-agency coordination and limited normative understanding at the operational level. The study recommends harmonizing employment-related legal documents, strengthening supervision and guidance by the Police and labor authorities, and enhancing the professionalism of security guards.